53‐1: Distinguished Student Paper: A Novel Low Power Gate Driver Architecture for Large 8K 120Hz LCD Display Employing IGZO Technology. Issue 1 (30th May 2018) - Iwase, Yasuaki; Tagawa, Akira; Takeuchi, Yohei; Watanabe, Takuya; Horiuchi, Satoshi; Asai, Yoshihiro; Yamamoto, Kaoru; Daitoh, Tohru; Matsuo, Takuya
Abstract : A novel low power gate driver architecture was developed for large 8K 120Hz LCD panel. For this application, not only high speed driving but also low power consumption is required. We employed a high mobility IGZO, dual VGL level driving method and gate driver circuit driven by DC supply. The simulation results show that our proposals meet 8K 120Hz driving requirements. Also, we have fabricated a prototype panel and confirmed high speed driving and low power consumption.